Molecular Characterization of HLA-B27 in Anterior Uveitis: Integrated Serological and Genetic Analysis Reveals Elevated Antigen Levels and Variants Concentrated in Exons 2 and 3 - Shinta Stri Ayuda Nur Setyaningsih; Arief Akhdestira Mustaram; Angga Fajriansyah; Patriotika Muslima; Elfa Ali Idrus; Muhammad Hamzah Syaifullah Azmi; Elsa Gustianty; Ernawati Arifin Giri-Rachman; Marselina Irasonia Tan (The Indonesian Biomedical Journal, 2026)
BACKGROUND: Anterior uveitis is the most common form of intraocular inflammation and an important cause of visual morbidity worldwide. Human leukocyte antigen B27 (HLA-B27) is a well-established immunogenetic risk factor; however, its molecular diversity remains insufficiently characterized in Indonesian populations. This study was conducted to characterize HLA-B27 at both the serological and genetic levels by quantifying serum antigen levels and identifying sequence variations in the HLA-B27 gene associated with anterior uveitis in Indonesian patients.METHODS: Thirteen anterior uveitis patients who were clinically evaluated through the Standardization of Uveitis Nomenclature (SUN) criteria were involved in this study. Blood sample was collected from subjects, and serum HLA-B27 concentrations were measured by enzyme-linked immunosorbent assay (ELISA). Genomic DNA was analyzed using combined Sanger and Oxford Nanopore sequencing. Variant calling and annotation were performed using a custom bioinformatics pipeline.RESULTS: Serum HLA-B27 antigen levels were significantly higher in anterior uveitis patients than in healthy reference controls. Sequence analysis identified 43 patient-exclusive variants after exclusion of shared polymorphic changes, from which 13 recurrent or potentially functionally relevant variants were prioritized for downstream analysis. These variants were predominantly distributed within exons 2 and 3 and comprised single-nucleotide substitutions, coding-region insertion–deletion events, and one promoter-region insertion. Several coding variants resulted in amino acid substitutions, while adjacent compensatory indel pairs were also identified among exon 2 frameshift-associated variants.CONCLUSION: Anterior uveitis is associated with both elevated circulating HLA-B27 antigen levels and sequence variation within functionally important regions of the HLA-B27 gene, particularly exons 2 and 3. The identified missense substitutions, coding-region indels, and promoter insertion suggest potential effects on peptide binding, molecular stability, immune interaction, intracellular protein handling, or transcriptional regulation.KEYWORDS: anterior uveitis, HLA-B27, genomic variants, peptide-binding groove, protein misfolding